Head Teachers’ Leadership Practices in Disability Management: A Case of Integrated Schools - Baraily, Khagendra (Scholars’ Journal, 2021)
This article explored how disability management practice is insighted by the head teachers of schools to address the diverse need of pupils in schools. The dimension of leadership practice on disability management is creating energy within school surrounding, securing learning environment in inclusive setting, extending the vision, enhancing capacity of teaching and non-teaching staff, conflict management, minimising the crisis and seeking improvement. This study employed the narrative inquiry design of qualitative method by using in-depth interview as a research tool to collect data. The sample was drawn purposively that comprised five head teachers of community secondary schools located in Kathmandu Valley. The result showed that head teachers emphasised specifically in infrastructural development, developing awareness about disabilities, creating inclusive atmosphere within organisation, need to focus on professional development along with inclusive indicators. Effective diversity management strategies are the major leading practices adopted by head teachers for the disability management. Its implication is that the leadership practice must be adapted within community schools to create quality and effective management for disability.